Culturally Grounded Scapegoating in Response to Illness and the COVID-19 Pandemic - Yang, Qian; Young, Isaac F.; Wan, Jialin; Sullivan, Daniel (Frontiers in Psychology, 2021)
For years, violence against doctors and healthcare workers has been a growing social issue in China. In a recent series of studies, we (Yang et al., under review) provided evidence for a motivated scapegoating account of this violence. Specifically, individuals who feel that the course of their (or their family member’s) illness is a threat to their sense of control are more likely to express motivation to aggress against healthcare providers. Drawing on existential theory (Rothschild et al., 2012), we propose that blaming and aggressing against a single individual represents a culturally afforded scapegoating mechanism in China. However, in an era of healthcare crisis (i.e., the global COVID-19 pandemic), it is essential to understand cultural variation in scapegoating in the context of healthcare. We therefore undertook two cross-cultural studies examining how people in the United States and China use different scapegoating responses to re-assert a sense of control during medical uncertainty. One study was conducted prior to the pandemic and allowed us to make an initial validating and exploratory investigation of the constructs of interest. The second study, conducted during the pandemic, was confirmatory and investigated mediation path models. Across the two studies, consistent evidence emerged that, both in response to COVID-related and non-COVID-related illness scenarios, Chinese (relative to U.S.) individuals are more likely to respond by aggressing against an individual doctor, while U.S. (relative to Chinese) individuals are more likely to respond by scapegoating the medical industry/system. Further, Study 2 suggests these culture effects are mediated by differential patterns of primary and secondary control-seeking.